Free Compass Math Practice on Polynomials - Sample 20

A set of questions, with answers, on polynomials are presented. These questions are similar to those in the compass math test and the answers to these questions are at the bottom of the page.

  1. If polynomials P(x) and Q(x) are given by P(x) = 3x2 + 2x - 1 and Q(x) = - x2 - 2x + 5,

    then P(x) - Q(x) =

    A) 2x2 - 6
    B) 4x2 + 4x + 4
    C) 3x2 + 4x - 6
    D) 4x2 + 4x - 6
    E) 4x2 + 4x - 4

  2. Polynomials P(x) and Q(x) are given by P(x) = 2x2 + 3x + 1 and Q(x) = 2 x2 + B x - x + 1 where B is a constant. Find B so that P(x) = Q(x).

    A) 0
    B) 1
    C) 2
    D) 3
    E) 4

  3. (2 x - 4)(3 x - 2) =

    A) 6x2 - 16x + 8
    B) -10x + 8
    C) 6x2 - 8x + 8
    D) 6x2 + 8x + 8
    E) 6x2 + 16x + 8

  4. Which of the following represents the product of 4 less than 3 times x and 3 more than twice x?

    A) (4 - 3x)(2x + 3)
    B) (3x + 4)(2x + 3)
    C) 6x2 - 2x - 12
    D) 6x2 + 2x - 12
    E) 6x2 - 2x + 12

  5. 3 x2 + 4x + 1 =

    A) (3x + 1)(x + 1)
    B) (x - 1)(3x - 1)
    C) (3x - 1)(x - 1)
    D) (x + 1)(3x + 1)
    E) (3x + 1)(x + 1)

  6. Polynomials P(x) and Q(x) are given by P(x) = - x2 + A x - 2 and Q(x) = (x - 2)(- x + 1) where A is a constant. Find A so that P(x) = Q(x).

    A) 0
    B) 3
    C) - 2
    D) 1
    E) - 3

  7. Which of the three polynomials are equivalent?

    (I) (2x + 2)(3x - 3) , (II) 6 x2 - 6 , (III) 6(x + 1)(x - 1)

    A) (I) and (III) only
    B) (II) and (III) only
    C) (I) and (II) only
    D) (I) , (II) and (III)
    E) None are equivalent polynomials

  8. If P(x) = 2x + 3 and Q(x) = - x - 2, then P(x) - 2 x Q(x) =

    A) 2x2 + 6x + 3
    B) 4x + 7
    C) - 2x2 - 2x + 3
    D) 2x2 - 6x + 3
    E) 2x2 + 6x - 3

  9. Which of these is not a polynomial?

    (I) 2 √x + 2
    (II) |x2 + 2| + 3
    (III) 2 x2 + 3x + 1
    (IV) x2 + x / (x + 1) + 2

    A) (II) and (IV) only
    B) (I) , (II) and (IV) only
    C) (I) , (II) , (III) and (IV)
    D) (I) and (II) only
    E) (III) only

  10. P(x) is a polynomial. If P(x) = - 4 x2 + 3, then P(x + 1) =

    A) - 4 x2 + 4
    B) x + 1
    C) - 4 x2 - 8x - 1
    D) - 4 x2 + x + 4
    E) x + 4

privacy policy